2022
DOI: 10.1021/acsenergylett.2c00274
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite/CIGS Tandem Solar Cells: From Certified 24.2% toward 30% and Beyond

Abstract: We demonstrate a monolithic perovskite/CIGS tandem solar cell with a certified power conversion efficiency (PCE) of 24.2%. The tandem solar cell still exhibits photocurrent mismatch between the subcells; thus optical simulations are used to determine the optimal device stack. Results reveal a high optical potential with the optimized device reaching a short-circuit current density of 19.9 mA cm −2 and 32% PCE based on semiempirical material properties. To evaluate its energy yield, we first determine the CIGS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
152
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(156 citation statements)
references
References 47 publications
4
152
0
Order By: Relevance
“…It should be noted that, for highly luminescent perovskite top cells, a correction to lower band-gap energies should be considered for the top absorber due to luminescent coupling. 30 , 31 Jošt et al 15 , 32 reported on the recent record 2T perovskite/CI(G)S TSC having an architecture very similar to that in this work with a certified efficiency of 24.2% for a band gap combination of ∼1.13 and ∼1.68 eV for the CI(G)S and perovskite, respectively. The PCE obtained from our simulations matches their experimental result well for this band-gap combination.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…It should be noted that, for highly luminescent perovskite top cells, a correction to lower band-gap energies should be considered for the top absorber due to luminescent coupling. 30 , 31 Jošt et al 15 , 32 reported on the recent record 2T perovskite/CI(G)S TSC having an architecture very similar to that in this work with a certified efficiency of 24.2% for a band gap combination of ∼1.13 and ∼1.68 eV for the CI(G)S and perovskite, respectively. The PCE obtained from our simulations matches their experimental result well for this band-gap combination.…”
supporting
confidence: 72%
“… 14 More recently, a certified PCE of 24.2% was achieved by replacing 2PACz with Me-4PACz and using defect passivation strategies on the perovskite top cell. 15 …”
mentioning
confidence: 99%
“…In recent years, in parallel to the surge in halide perovskite solar cells’ efficiency, a significant research effort has been directed at coupling low-cost photovoltaic (PV) technologies with large (1.6–1.8 eV) and medium (∼1.1 eV) optical absorption thresholds. 3–5 However, research on devices for the short-wavelength IR region (0.7–0.95 eV) is still lagging, partly due to the limited availability of low-cost and non-toxic absorber materials. For example, Ge ( E g = 0.66 eV), 6 and III–V semiconductors, such as GaSb (0.72 eV) 7,8 and GaInAs, 9 are current small band gap semiconductors used in triple-junction solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Stacking three photovoltaic (PV) devices with complementary light-absorbing materials with bandgaps of 1.83 eV, 1.6 eV, and 0.71 eV theoretically facilitates solar-to-electricity power conversion efficiency (PCE) of ∼50%. 1–3 In parallel to advancements in coupling Si and other thin-film photovoltaic devices with “large” bandgap halide perovskite solar cells for making efficient tandem PV devices, 4–7 there is a need for complementary low-cost small bandgap absorber materials for the short-wavelength infrared section, where an additional 5–6% absolute PCE points can be gained. 8–12 Current triple-junction solar cells use either Ge ( E g = 0.66 eV), 13 GaSb ( E g = 0.72 eV), 14,15 or GaInAs 16 as a small bandgap absorber material.…”
Section: Introductionmentioning
confidence: 99%